(untitled) - Chirol, Valentine (London)
This book introduce the bedrock of hinduism. The governing principles of British rule. The flowing tide of Western influence. The firt wave of anti-western reaction. The partition of Bengal. The tangle of western education...
Keywords: Ấn Độ,India; Chính trị và chính phủ,Politics and government; 1765-1947,1765-1947